2016
DOI: 10.3390/ijms17060958
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Innate Immune Response to Improve Cardiac Graft Recovery after Heart Transplantation: Implications for the Donation after Cardiac Death

Abstract: Heart transplantation (HTx) is the ultimate treatment for end-stage heart failure. The number of patients on waiting lists for heart transplants, however, is much higher than the number of available organs. The shortage of donor hearts is a serious concern since the population affected by heart failure is constantly increasing. Furthermore, the long-term success of HTx poses some challenges despite the improvement in the management of the short-term complications and in the methods to limit graft rejection. My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 152 publications
(305 reference statements)
2
38
0
Order By: Relevance
“…Cold storage disrupts cellular homeostasis and leads to ATP depletion, fluid stasis, edema, and reperfusion injury. Prolonged time in a nonhomeostatic environment exacerbates damage and risks tissue viability 4,10,11 . Compared to other solid organ transplants, the heart is especially sensitive to the effects of cold ischemic storage 4,10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Cold storage disrupts cellular homeostasis and leads to ATP depletion, fluid stasis, edema, and reperfusion injury. Prolonged time in a nonhomeostatic environment exacerbates damage and risks tissue viability 4,10,11 . Compared to other solid organ transplants, the heart is especially sensitive to the effects of cold ischemic storage 4,10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…31 Several inflammatory pathways are activated both before and after HTX, including infiltrating cells like neutrophils and lymphocytes, inflammatory cytokines like IL-1 and IL-18, the NLRP3 inflammasome, and toll-like receptor activation. 31,32 Experimental studies have shown that modulating the innate inflammatory response is associated with improved survival after HTX, yet there is no specific approved treatment in this direction. Our study confirms the association between increase innate inflammation and worse outcome in HTX and strengthens the need for specific treatments.…”
Section: Discussionmentioning
confidence: 99%
“…To restore the intrinsic function of cardiac tissue, heart transplantation has been the only option . As mentioned earlier, heart transplantation is limited owing to the low availability of heart donors and the high risk of immune response . Hence, cell‐based therapies have gained attention for their capability to treat damaged cardiac tissue .…”
Section: Soft Bioelectronics–assisted Tissue Engineeringmentioning
confidence: 99%